Industria de la construcción en el Ecuador: auge, cambios y crisis - Quevedo Uvidia, Jorge Andrés (2018)
This project addresses the debates and current situation of the construction industry in Ecuador, the discourses related to this issue and the problems facing real estate companies and citizens related to this field. An approach is made to the importance of this sector for the national economy and its position with respect to the other strategic sectors. In addition, the current situation is considered, considering the changes in the laws that regulate the price of land and other regulations that have caused controversy in the country such as the Goodwill Law, considering the positions of different institutions and related actors. To this end, interviews were conducted with directors of construction chambers, analysts, assembly members, real estate developers, lawyers, representatives of public-private financial institutions and testimonies of citizens were collected. Issues related to the boom and crisis of the construction sector were also addressed, considering the change in policies and regulations. This research shows the factors that contributed to the boom and crisis experienced by the construction industry in recent years as well as the future projection and its implications.